2020
DOI: 10.1212/nxi.0000000000000734
|View full text |Cite
|
Sign up to set email alerts
|

Rituximab, MS, and pregnancy

Abstract: ObjectiveTo describe the safety and efficacy of rituximab (RTX) in MS and pregnancy, we conducted a retrospective cohort study of 74 pregnancies among 55 women treated with RTX for MS and their offspring.MethodsWe used prospectively collected information from the electronic health record at Kaiser Permanente Southern California between 2012 and 2019 of mother and baby to identify treatment history, pregnancy outcomes, and relapses.ResultsLast RTX exposure before conception occurred between 1.8 and 5.2 months i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
62
2
2

Year Published

2020
2020
2022
2022

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 67 publications
(68 citation statements)
references
References 38 publications
2
62
2
2
Order By: Relevance
“…Although the overall risk of PB was similar to other studies, 2,24 we found a higher risk for PB (45%) and lower birth weight when anti-CD20 mAb was given during pregnancy. This might be partially related to the underlying disease and/or concomitant autoimmune diseases, 25 especially in NMOSD, to the previous DMT exposure and/or other concomitant medication with steroids, and deserves further investigation.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…Although the overall risk of PB was similar to other studies, 2,24 we found a higher risk for PB (45%) and lower birth weight when anti-CD20 mAb was given during pregnancy. This might be partially related to the underlying disease and/or concomitant autoimmune diseases, 25 especially in NMOSD, to the previous DMT exposure and/or other concomitant medication with steroids, and deserves further investigation.…”
Section: Discussionsupporting
confidence: 89%
“…14,15 Anti-CD20 mAbs could be an interesting option as in contrast to other drugs, no rebound has been reported so far. 2,16 Therefore, the objective of this cohort study was to investigate the safety of RTX/ocrelizumab (OCR) during the last 12 months before or during pregnancy in women with neuroimmunologic diseases and to assess DA in a subcohort of women with RRMS or NMOSDs.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“… 25 Thus, our study provides evidence and supports that RTX may be the preferred choice of therapy for women with MS considering pregnancy. A few studies provide further assurance, as they concluded that there have been no major safety concerns associated with RTX use during pregnancy 16 , 26 ; however, these were based on a small number of women, and future studies focused on safety, such as risk of malformation or stillbirth, should be conducted to confirm findings.…”
Section: Discussionmentioning
confidence: 99%
“…A study of 74 pregnancies in Kaiser Permanente patients with MS showed no increase in adverse perinatal outcomes over expected population rates. [ 14 ]. The largest dataset available comes from the rituximab global drug safety database maintained by Biogen Idec/Genentech/Roche [ 2 ].…”
Section: Discussionmentioning
confidence: 99%